Energy and exergy evaluation of rice processing mills working with biomass gasifier in parboiling process. (1st January 2020) - Beno Wincy, W.; Edwin, M.; Joseph Sekhar, S.
Highlights: I-Law and II-Law Thermodynamic performance of Rice Husk Fuelled Biomass Gasifier Operated Gas Fired Boiler is evaluated. Overall energy and exergy efficiencies are calculated as 52.16% and 29.48%respectively. Combustor has the highest exergy destruction in the boiler of 65%. Minimum Potential Improvement (PI) as 1.16 MW at the Equivalence Ratio (ER) of 0.2. Abstract: Rice processing is an energy intensive area as it consumes huge amount of thermal energy for parboiling and drying, moreover, such industries are facing serious problems like poor system efficiency and environmental impacts due to the direct combustion of biomass. Improving energy and exergy efficiencies of the system can reduce such problems, however, it is essential to pin point the area at which the losses occur. This paper presents energy and exergy analysis of gasifier operated and producer gas fired boiler system with rice husk as energy source for parboiling and drying of paddy. The maximum gasifier efficiency and Calorific Value (CV) of the producer gas were 78% and 4.96 MJ Nm −3 respectively at the Equivalence Ratio (ER) of 0.2 with the corresponding gasification temperature of 1023 K. The combustor contributes about 65% of exergy destruction followed by the heat exchanger in the producer gas fired boiler. The overall energy and exergy efficiencies of the system were observed as 52.16% and 29.48% respectively. In addition, exergy destruction, specific entropy generation and sustainability index were also examined. From the results it is identified that the gasifier operated gas fired boiler system is superior in its energy and exergy aspects than the conventional paddy processing systems which can reduce the fuel consumption and environmental impacts of rice processing mills.